Enhancing verbal episodic memory in older and young subjects after non-invasive brain stimulation - Manenti, Rosa; Brambilla, Michela; Petesi, Michela; Ferrari, Clarissa; Cotelli, Maria (Frontiers in Aging Neuroscience, 2013)
Memory is the capacity to store, maintain and retrieve events or information from the mind. Difficulties in verbal episodic memory commonly occur in healthy aging. In this paper, we assess the hypothesis that anodal transcranial direct current stimulation (tDCS) applied over the dorsolateral prefrontal cortex (DLPFC) or over the parietal cortex (PARC) could facilitate verbal episodic memory in a group of 32 healthy older adults and in a group of 32 young subjects relative to a sham stimulation using a single-blind randomized controlled design. Each participant underwent two sessions of anodal tDCS (left and right) and one session of sham stimulation. Overall, our results demonstrated that, in young and in older subjects, anodal tDCS applied during the retrieval phase facilitates verbal episodic memory. In particular, we found that tDCS applied over the left and right regions (DLPFC and PARC) induced better performance in young participants; only tDCS applied over the left regions (DLPFC and PARC) increased retrieval in older subjects. These results suggest that anodal tDCS can be a relevant tool to modulate the long-term episodic memory capacities of young and older subjects.